Earthworm, infiltration, and tillage relationships in a dryland pea–wheat rotation - Wuest, Stewart B (Applied soil ecology : a section of Agriculture, ecosystems & environment, 2001)
Dryland farming in the Mediterranean climate of the Pacific Northwest, USA supports extremely low earthworm populations under conventional tillage. Increases in earthworm populations are being observed in fields under no-till cropping systems. A 30+ year experiment with four tillage levels in a pea ( Pisum sativum L.)-winter wheat ( Triticum aestivum L.) rotation was evaluated for earthworm populations and ponded infiltration rates. Where tillage has been limited to 2.5 cm depth, Apporectodea trapezoides (Duges) mean population was 25 m −2. Plots subject to tillage by plow (25 cm depth) or chisel (35 cm depth) averaged less than 4 earthworms m −2. The shallow tillage treatment also had the highest average infiltration rate of 70 mm h −1 compared to 36 for chisel, 27 for spring plow, and 19 mm h −1 for fall plow treatments. The highly variable nature of earthworm counts and infiltration measurements prevented conclusive correlation between the two, but increases in both can be attributed to minimum tillage.